Penguatan Kompetensi Guru Bahasa Indonesia dalam Perancangan Pembelajaran Kontekstual Berbasis Kearifan Lokal di SMAN 5 Ambon - Latupapua, Falantino Eryk; Pesiwarissa, Leonora Farilyn (Universitas Pattimura, 2024)
The purpose of this community service activity is to strengthen the professional competence of Indonesian language teachers at SMAN 5 Ambon in designing contextual learning based on local wisdom. Contextual learning that is integrated with local cultural values is considered to be able to increase the relevance of teaching materials and shape the character of students who love local culture. The target of this activity is Indonesian language teachers at SMAN 5 Ambon who are active in teaching and show commitment to developing innovative learning strategies. The method of activity implementation includes identification of partner needs through an initial survey, training through workshops, focus group discussions (FGDs), and direct assistance in the preparation of learning tools in the form of contextual lesson plans based on Maluku local wisdom. Activities were carried out offline with a participatory, collaborative, and reflective approach. The results of the activities showed a significant increase in teachers' understanding and skills in designing contextual learning. Based on the analysis of evaluation questionnaire data with a descriptive statistical approach, the average competency improvement score was 87.9%, which indicates a very good category. All participants also stated that this activity was very relevant and applicable to be applied in daily learning. In addition, the lesson plans show the integration of local cultural values explicitly and creatively. Based on the analyzed questionnaire results, it can be concluded that training based on contextual approaches and local culture is effective in improving teachers' pedagogical competencies. This competency strengthening also contributes to cultural preservation efforts through education and encourages the realization of a more meaningful and humanistic learning process in Indonesian language classes.